The effect of age on peripheral stem cell mobilization in healthy donors, single center experience. Issue 1 (9th March 2016) - Ozen, Mehmet; Gunduz, Mehmet; Topcuoglu, Pervin; Toprak, Selami K.; Dalva, Klara; Gurman, Gunhan; Ilhan, Osman
Abstract : Purpose : Peripheral stem cell transplantation is used as a life‐saving therapeutic option in hematological malignancies. As previously established, most hematological malignancies are seen in the elderly population. Therefore, possible HLA‐identical sibling donors of elderly patients are generally of an advanced age. In this study, we aimed to evaluate the effect of old age on stem cell mobilization and quality in older adult healthy sibling donors.Materials and Methods : Between 2006 and 2014, we evaluated 38 healthy donors aged ≥55 years. The granulocyte‐colony stimulating factor (G‐CSF) analogs were used at a dose of 5 µg/kg/day and administered subcutaneously twice a day for five days. CD34+ cells were estimated in the peripheral blood before collection of the apheresis product. The National Marrow Donor Program selects healthy unrelated donors if they are younger than 60 years. Therefore, we compared the product quality in donors over the age of 60 to that in donors aged 60 years or less.Results : We collected sufficient products from all the donors with one to three apheresis procedures. No serious complication was detected in all donors. Reaching the target CD34+ cell count in one day were detected in 83% of younger and 79% of older donors ( P = NS). Collected CD34+ cells x10e6/recipient body weight (kg) was same and 5.1 in the groups ( P = NS). There were no correlation between the donor age and these parameters.Conclusion : Healthy donor apheresis in older adults can be performed effectively and possible donors should be evaluated regardless of their age. J. Clin. Apheresis 32:16–20, 2017. © 2016 Wiley Periodicals, Inc.